The Influence of Sharia Good Corporate Governance on Financial Performance (ROA) Of Sharia Banking In Indonesia for the 2016-2020 Period - Ari Kurniawan Putra (Universitas Bunda Mulia, 2023)
This study aims to determine the partial effect of Good Corporate Governance with the following indicators; board of directors, board of commissioners, audit committee, and board of sharia supervisory, on financial performance using financial ratios, namely ROA (return on assets) during the 2016-2020 period. The population in this study is Islamic banking companies listed on the Indonesia Stock Exchange. The determination of the sample using purposive sampling included as many as 11 samples of companies in 5 years. The data analysis technique used in this research is multiple regression analysis using the panel data method. The results of the study indicate that partially the board of directors and the board of commissioners affect the financial performance, while the audit committee and sharia supervisory board do not affect the financial performance. Besides, the indicators of Good Corporate Governance (board of directors, board of commissioners, audit committee, board of sharia supervisory) simultaneously affect the financial performance with the value of R square indicating that variable X has a large contribution to variable Y.